Technological aspects of obtaining spineless cactus [Nopalea cochenilifera (L.) Salm-Dyck] bud flour after drying - Pereira, Emmanuel Moreira [UNESP]; da Silva, Nathan José Pereira [UNESP]; de Sousa, Hyago Costa [UNESP]; Mattiuz, Ben-Hur [UNESP]; Filho, Carlos Roberto Marinho da Silva [UNESP] (Southern Cross Publishing, 2017)
The spineless cactus has high production of green matter. Its major importance is utilized for production of flour in agro-industrial processes as well as its nutritional characteristics. The objective of this work was to evaluate the quality of the flour of the spineless cactus bud produced under different temperatures and to describe the drying process by means of mathematical models. The spineless cactus genotype 'Miúda' (Nopalea cochenilifera (L.) Salm-Dyck) was used in this study. The buds approximately with 20 cm in length were harvested. Drying was carried out at different temperatures (55, 65, 75 and 85 ° C). Evaluations were done with the application of mathematical models to the data obtained from the drying kinetics, using determination of coefficients (R2) and chi-square (χ2). The chemical and toxicological composition of flour was evaluated. The temperature treatments influenced the flour quality. The flour obtained at the temperature of 55 ° C presented the best chemical percentages and showed no toxic effect. The studied models presented good statistical indices as a function of the adjustments to the experimental data. The Wang and Singh model presented the best R2 and χ2 for the drying kinetics of the palm shoots. The Peleg model presented a unique graphical behavior, reaching to cross the field of negative water quantity before reaching the equilibrium point of the dehydration process. Therefore, this model cannot be used to simulate the drying process of 'Miúda' shoots within the studied temperature range.
Keywords: Cactaceous; Mathematical modeling; Nopalea; Quality; Toxicity